Simplifying both sides of the equation then isolating the variable
Answer:
3. 3(x+y)(x-y)
4. (y²+4)(y+2)(y-2)
5. 2(3x+1)(x+2)
Step-by-Step:
3. 3(x²-y²) = 3(x+y)(x-y)
4. y⁴-16 = (y²+4)(y²-4)= (y²+4)(y+2)(y-2)
5. 6x²+14x+4 = 2(3x²+7x+2) = 2(3x+1)(x+2)
PLEASE RATE!!! I hope this helps!!!
If you have any question comment below
(I have verified my answers on an online calculator)
Answer: A
Step-by-step explanation:
11.3-7.2f = -3.82
-11.3 -11.30
_____________
-7.2f = -15.12
____ _____
-7.2 -7.2
f = 2.1
2 is the answer 23:35677544